On Supersaturated Semigroups - Noor Alam; Noor Mohammad Khan (Journal of Advances in Applied & Computational Mathematics, 2015)
In this paper, we prove the long known open problem and converse part of the Higgin’s result that any globally idempotent ideal of a supersaturated semi-group is supersaturated.